The needs of family caregivers providing palliative home care in Portugal: a multi-stage mixed methods study protocol - Laranjeira, Carlos; Dixe, Maria dos Anjos; Coelho, Alexandra; Reigada, Carla; Carneiro, Rui; Querido, Ana (Frontiers in Public Health, 2025)
BackgroundIn palliative care (PC), family caregivers (FCs) play an important role in managing patient symptoms and addressing patient needs. In end-of-life (EoL), FCs frequently experience distress that exacerbates emotional strain and complicates grieving. Training FCs to care for palliative patients should be implemented urgently, enhancing their preparation, reducing their burden, and assuring Quality of Life (QoL) throughout illness progression. Recent research has highlighted a global shift toward death in the community, in line with patient preferences. In contrast, the Portuguese reality reveals a tendency to die in hospitals and an absence of community PC and support for FCs, a model that might not be sustainable in the future.AimsThe overall aim of this study is to comprehensively assess the unmet needs of FCs in home-based PC settings and their experiences interacting with PC services, and to propose strategies and recommendations for FC advocacy in PC.MethodsA multi-stage mixed-methods design will be used, divided into four main phases. Phase I will identify unmet needs and profile FCs through a quantitative cross-sectional analysis of a nationally representative sample. Phase II will develop a qualitative study to understand the role and impact of FCs providing PC and their experiences with support from PC services. This will help generate ideas for more accessible and sustainable PC-in-place. Phase III will comprise a multi-phased, consensus-based approach to identify priority areas of need, as decided by FCs and professionals, and develop a short Caregivers Assessment Tool (CAT). Lastly, phase IV will synthesize the results and produce a white book for FC advocacy in PC.DiscussionThe project will enrich community PC while optimizing social welfare activities. By identifying the unmet requirements of FCs of PC patients, the initiative will enhance the QoL and well-being of the care recipients, respecting their preferences, while improving the health and competence of FCs, and minimizing the consumption of hospital resources. Lastly, FC engagement should be coordinated and sustainably executed through the participation of relevant all stakeholders.